2016
DOI: 10.1016/j.bbr.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A single low dose of valproic acid in late prenatal life alters postnatal behavior and glutamic acid decarboxylase levels in the mouse

Abstract: Rationale Rodents exposed to valproic acid (VPA) in prenatal life exhibit post-natal characteristics analogous to autism spectrum disorder (ASD). Many previous studies used relatively high doses of VPA during early pregnancy, potentially confounding interpretation because the offspring are the "survivors" of a toxic insult. Low dose or late gestation exposure has not been widely studied. Objectives We examined the behavioral sequelae of late gestation exposure to low dose VPA in the mouse. We also examined pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…Specifically, we exposed pregnant mice to poly(I:C), a synthetic mimetic of viral dsRNA analog, a well-documented mouse model of MIA. We and others have reported that poly(I:C)-induced MIA precipitates altered brain and behavioral phenotypes in offspring that mirror abnormalities observed in ASD and related neurodevelopmental conditions such as schizophrenia (Meyer et al, 2006 ; Li et al, 2015 ; Wei et al, 2016 ; Wu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 75%
“…Specifically, we exposed pregnant mice to poly(I:C), a synthetic mimetic of viral dsRNA analog, a well-documented mouse model of MIA. We and others have reported that poly(I:C)-induced MIA precipitates altered brain and behavioral phenotypes in offspring that mirror abnormalities observed in ASD and related neurodevelopmental conditions such as schizophrenia (Meyer et al, 2006 ; Li et al, 2015 ; Wei et al, 2016 ; Wu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 75%
“…Interestingly, older ages in the VPA groups had decreased social [66] and total [67] exploration than younger VPA-exposed rodents. Older VPA-exposed rodents had a lower discrimination index in the novel object recognition test compared to younger VPA rodents [68]. This difference in discrimination could have played a role in older VPA rodents' social novelty preference impairment.…”
Section: Age Differencesmentioning
confidence: 85%
“…Although many studies have investigated the role of GABAergic signaling in rodent neural development and behaviors relevant to autism (Tabuchi et al, 2007 ; Cusmano and Mong, 2014 ; Lauber et al, 2016 ; Olexová et al, 2016 ; Wei et al, 2016 ; Chau et al, 2017 ; Watanabe et al, 2017 ), the behavioral ontogeny as determined by changes in GABAergic system of different brain regions is poorly characterized. Here, we employed a VPA rat model of autism to investigate the autism-like behaviors and GABAergic GAD67 expression underlying these altered behaviors in multiple brain areas at the developmental stages from birth to adulthood.…”
Section: Introductionmentioning
confidence: 99%